2010
DOI: 10.1210/jc.2009-2575
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Testosterone Therapy in Adult Men: A Systematic Review and Meta-Analysis

Abstract: The adverse effects of testosterone therapy include an increase in hemoglobin and hematocrit and a small decrease in high-density lipoprotein cholesterol. These findings are of unknown clinical significance. Current evidence about the safety of testosterone treatment in men in terms of patient-important outcomes is of low quality and is hampered by the brief study follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
458
10
15

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 634 publications
(507 citation statements)
references
References 70 publications
21
458
10
15
Order By: Relevance
“…The reduction in HDL levels may be explained by a reported testosteroneinduced decrease in lipoprotein lipase activity in humans (Rebuffe-Scrive et al 1991), but the mechanism underlying testosterone-induced decrease in HDL levels has not been clarified. Our data were consistent with a meta-analysis (Whitsel et al 2001) and a recent systematic review (Fernandez-Balsells et al 2010) that reported a significant small decrease in HDL cholesterol levels in men treated with testosterone; however, a meta-analysis found no change in HDL cholesterol levels in response to testosterone treatment (Isidori et al 2005). A low HDL is linked to an increased morbidity and mortality of cardiovascular disease, and in a recent study on old men with limitations in mobility, cardiovascular and respiratory events were significantly increased during testosterone therapy compared to placebo (Basaria et al 2010).…”
Section: Discussionsupporting
confidence: 92%
“…The reduction in HDL levels may be explained by a reported testosteroneinduced decrease in lipoprotein lipase activity in humans (Rebuffe-Scrive et al 1991), but the mechanism underlying testosterone-induced decrease in HDL levels has not been clarified. Our data were consistent with a meta-analysis (Whitsel et al 2001) and a recent systematic review (Fernandez-Balsells et al 2010) that reported a significant small decrease in HDL cholesterol levels in men treated with testosterone; however, a meta-analysis found no change in HDL cholesterol levels in response to testosterone treatment (Isidori et al 2005). A low HDL is linked to an increased morbidity and mortality of cardiovascular disease, and in a recent study on old men with limitations in mobility, cardiovascular and respiratory events were significantly increased during testosterone therapy compared to placebo (Basaria et al 2010).…”
Section: Discussionsupporting
confidence: 92%
“…102 It has been also reported that testosterone accelerates vascular remodeling 119 and stimulates renal prohypertensive processes, including the renin-angiotensin-aldosterone system. 120 Recent metaanalyses have revealed that CVD events were not different between testosterone and placebo groups, 86,121 indicating the complexity of testosterone therapy, as was shown for estrogen therapy in women.…”
Section: Possible Harmful Effects Of Testosterone On Blood Vesselsmentioning
confidence: 97%
“…The testosterone-treated men were at a higher risk of developing erythrocytosis than the placebo/nonintervention group. The adverse effects of testosterone therapy include an increase in hemoglobin and hematocrit (5). A meta-analysis of 51 studies revealed that TRT is associated with an average 0.8 g/dl increase in Hb and a 3.2 % increase in Ht, but there was no signifi cant effect on mortality, prostate size or cardiovascular outcomes (5).…”
Section: Discussionmentioning
confidence: 99%